Transplantation of a three-lobed donor left lung: A case report. (February 2019) - Jacob, Samuel; Makey, Ian A; El-Sayed Ahmed, Magdy M; Mallea, Jorge M; Erasmus, David B; Belli, Erol V
A true left middle lobe (lingular lobe) is very rare, but accessory fissures can be unexpectedly found at transplant. Pre-transplant knowledge of accessory lobes and accessory fissures aids in preparation, transplantation, postoperative assessment, and long-term care planning; however, fissures and accessory lobes can be overlooked by radiologists during routine evaluation of images. Here, we describe the first left lung with three anatomical lobes that was successfully transplanted into a 63-year-old patient with idiopathic pulmonary fibrosis. This anatomical variation did not change our surgical plan or technique, but surgeons should be aware of this possibility, especially when planning postoperative care.